(untitled) (Damascus University Journal for legal sciences, 2024)
This research deals with the issue of identifying the commitment by abstaining and the way of compensation. Commitment to abstain—sometimes called negative commitment—is the commitment under which a given person refrains from doing an act that he is normally permitted to do in the absence of the commitment. This may include public freedoms such as the right to work and the right to competition. Public freedoms are characterized that everyone is equally entitled to without any exclusion. Compensation occurs when someone is committed to be abstained from exercising his or her public freedoms without taking it away or breaching it from the permanently committed, being protected by law which no one is allowed to breach. The commitment might be unique to abstinence as it may be something associated with him/her only and does not relate to others. Something like, say, his/her right to use own property. This is when composition occurs when a person shows commitment to be abstained to do something—temporarily though— that he normally can do. However, when abstinence is eternal, the matter goes beyond the limits of the obligation to become right forfeiture or waiver of the right.